ASUHAN KEPERAWATAN PADA KASUS PASIEN DIARE KRONIS DISERTAI DEHIDRASI RINGAN–SEDANG DI IGD RSUP DR. SARDJITO YOGYAKARTA - Tira Kamisah; Wawan Febri Ramdhani (JOURNAL SAINS STUDENT RESEARCH, 2026)
Chronic diarrhea is a condition that can lead to fluid and electrolyte imbalance if not managed optimally, one of which is mild-to-moderate dehydration. This Final Scientific Work for Ners (KIAN) aims to describe the application of nursing care in patients with chronic diarrhea accompanied by mild-to-moderate dehydration through a case study approach. The method used is a case study with a descriptive approach on one adult patient hospitalized. Data collection was carried out through a comprehensive nursing assessment including interviews, observation, physical examination, as well as review of medical records and supporting examination results. The assessment results showed that the patient experienced complaints of weakness, diarrhea, nausea, and vomiting with objective findings of decreased skin turgor, dry oral mucosa, increased pulse rate, and laboratory results indicating hypokalemia and metabolic disturbances. Based on data analysis, the main nursing diagnoses established were fluid volume deficit, electrolyte imbalance, and nausea. Nursing interventions were developed based on the Indonesian Nursing Diagnosis Standards (SDKI), Indonesian Nursing Outcomes Standards (SLKI), and Indonesian Nursing Intervention Standards (SIKI), which included monitoring fluid and electrolyte status, collaboration in providing fluids and medications, and health education. Evaluation showed improvement in the patient's condition, characterized by stable vital signs, reduced complaints of nausea, and increased tolerance to fluid intake. Comprehensive and continuous nursing care plays an important role in supporting the recovery of patients with chronic diarrhea accompanied by mild-to-moderate dehydration.